AN OUTSTANDING TEACHER, SCINTISTS IN GEOMORPHOLOGY AND TECTONICS: TO 110TH ANNIVERSARY OF ACADEMICIAN V.G. BONDARCHUK - Shatalov, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
To the 110thanniversary of Academician Volodymyr Bondarchuk. The article deals with the genius Ukrainian scientist-geologist, founder of a new scientific field, talented theoreticians and practitioners Academician Vladimir Gavrilovich Bondarchuk. The main stages of this life and researches are considerd.